2019
DOI: 10.1002/sia.6622
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatments on the localized corrosion resistance of the AA2198‐T8 aluminum lithium alloy welded by FSW process

Abstract: In this work, the effect of eight types of surface treatments on the corrosion resistance of friction stir welded samples of an AA2198‐T8 Al‐Cu‐Li alloy were tested and compared in an attempt to find suitable alternatives to toxic and carcinogenic hexavalent chromium treatments. All the samples were anodized and subjected to different post‐anodizing treatments. The post‐anodizing treatments were (1) hydrothermal treatment in Ce (NO3)3 6H2O solution; (2) hydrothermal treatment in Ce (NO3)3 6H2O solution with H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…23 In the present F I G U R E 1 5 XPS high resolution spectra: (A) Si2p for polished AA 2198 T8 coated with BTSE and (B) for unpolished AA2198 T8 coated with BTSE, (C) Mg1s for unpolished AA2198 T8 coated with BTSE, and (D) Li1s for unpolished AA2198 T8 coated with BTSE study, it is suggested that the poor corrosion protection ability of the unpolished samples coated with BTSE is caused by the heterogeneous surface related to the highly active surface corresponding to Mg-enriched bands regions of the unpolished samples, Figure 3, leading to preferential sites for localized corrosion. 22,23,37,58 The XPS signal for the unpolished sample showed more intense peaks for Mg and Li as expected, and it resulted in a surface electrochemically more active than the polished one, as showed in the SECM maps, Figure 12C,D.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…23 In the present F I G U R E 1 5 XPS high resolution spectra: (A) Si2p for polished AA 2198 T8 coated with BTSE and (B) for unpolished AA2198 T8 coated with BTSE, (C) Mg1s for unpolished AA2198 T8 coated with BTSE, and (D) Li1s for unpolished AA2198 T8 coated with BTSE study, it is suggested that the poor corrosion protection ability of the unpolished samples coated with BTSE is caused by the heterogeneous surface related to the highly active surface corresponding to Mg-enriched bands regions of the unpolished samples, Figure 3, leading to preferential sites for localized corrosion. 22,23,37,58 The XPS signal for the unpolished sample showed more intense peaks for Mg and Li as expected, and it resulted in a surface electrochemically more active than the polished one, as showed in the SECM maps, Figure 12C,D.…”
Section: Discussionsupporting
confidence: 65%
“…Many authors have reported that the NSDL affects the corrosion behavior of different Al alloys, 41,52–57 although the influence of this layer on the third (new) generation of Al–Cu–Li alloys has been rarely reported 23 . In the present study, it is suggested that the poor corrosion protection ability of the unpolished samples coated with BTSE is caused by the heterogeneous surface related to the highly active surface corresponding to Mg‐enriched bands regions of the unpolished samples, Figure 3, leading to preferential sites for localized corrosion 22,23,37,58 . The XPS signal for the unpolished sample showed more intense peaks for Mg and Li as expected, and it resulted in a surface electrochemically more active than the polished one, as showed in the SECM maps, Figure 12C,D.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…[14][15][16][17][18] Among these coatings, Ce conversion coating is a promising alternative to Cr (VI) conversion coating due to its unique properties such as environmental friendliness, high adhesive strength to the substrate, and excellent corrosion resistance. 19,20 In recent years, considerable efforts have been devoted to improving the corrosion resistance of Ce-based coatings on metal substrates. Ramezanzadeh et al 21 used zinc phosphate conversion coating as a sealing agent for posttreatment of Ce-based coating, and the resulting coating was compact with less cracks and with better corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Surface mechanical attrition treatment (SMAT) is one among the efficient techniques to improve the surface strength by refining the grain size leading to nanograins formation [ 30 , 31 ]. In addition, the severe plastic deforming of materials by various methods leads to grain refinement to the desired level and enhances the mechanical properties without affecting the surface chemical behavior to a large extend [ 32 37 ].…”
Section: Introductionmentioning
confidence: 99%